Effects of increased phosphorus fertilizer on C, N, and P stoichiometry in different organs of bluegrass (Poa L.) at different growth stages - Wang, Jiahao; He, Keyan; Bao, Gensheng; He, Lin; Xu, Hang; Song, Meiqi; Jin, Ling; Wei, Xiaoxing (Frontiers in Ecology and Evolution, 2023)
Abstract: Application of phosphorus (P) fertilizer can promote photosynthesis in forage grasses and accelerate their establishment. To improve the utilization efficiency of P fertilizer for bluegrass (Poa L.) in alpine regions. The effects of P fertilizer on their growth, and on carbon(C), nitrogen (N) and P distribution in different organs of them are tested at six P fertilization levels (3, 6, 9, 12, 15, 18 g·m-2). The results showed: (1) Nutrient content in each organ of bluegrass varies during different growth stages, with the lowest nutrient content occurred in the wilt stage. (2) The response of nutrient content and ratio of each organ of bluegrass to different P fertilization levels varies. When the P application rate was 15 g·m-2, the contents of N and P in roots were the highest, and their C/N and C/P ratios were the lowest. When the P application rate was 12 g·m-2, the contents of N and P in stems were the highest, and their C/N and C/P ratios were the lowest. When the P application rate was 9 g·m-2, the contents of N and P in leaves were the highest, and their C/N and C/P ratios were the lowest. When the P application rate was 6 g·m-2 the contents of N and P in the panicle were the highest, and their C/N and C/P ratios were the lowest. These results provide a better understanding for the effect of P fertilization on the nutrient partitioning pattern of perennial forage plant organs in alpine regions. In formation from this study can support a more reasonable P fertilization for the establishment of early grassland. For example, in artificial forage grassland, the application of low-concentration P fertilizer (6~9 g·m-2) can promote the nutrient content spikes and stems of forage grass; for ecological management, the application of high-concentration P fertilizer (15 g·m-2) can promote nutrient content in roots and enhance the ecological benefits of forage grassland.